Father of Persian Verse Rudaki and his Poetry - Tabatabai, Sassan (Iranian Studies Series, 2010)
Abu 'Abdollâh' Jafar ibn Mohammad Rudaki (c. 880 CE-941 CE) was a poet to the Samanid court which ruled much of Khorâsân (northeastern Persia) from its seat in Bukhara. He is widely regarded as the father of Persian poetry, for he was the first major poet to write in New Persian language, following the Arab conquest in the seventh and eighth centuries, which established Islam as the official religion, and made Arabic the predominant literary language in Persian-speaking lands for some two centuries. This book presents Rudaki as the founder of a new poetic aesthetic, which was adopted by subsequent generations of Persian poets. Rudaki is credited with being the first to write in the rubâi form; and many of the images we first encounter in Rudaki's lines have become staples of Persian poetry.